Implementation The Indonesian Electronic Identity Card Policy in The Office of Population's Civil Registration Minahasa regency - Koagouw, Enjel Maria; Kairupan, Sisca Beatrix; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
The implementation of e-Government in public services using technology and information currently being implemented in the government sector is an electronic identity card. Implementing the electronic identity card policy is a program to implement the Single Identify Number. Every resident who meets the age requirements only has one identity called the Population Identification Number (NIK) until death. The purpose of this study is to focus on the description process related to the implementation of the Electronic Identity Card Policy at the Minahasa Regency Population and Civil Registration Office, namely How the Mechanism of the Electronic Identity Card Activity Program at the Minahasa Regency Population and Civil Registration Office. The research used is a qualitative descriptive research type. The data collection technique used is a combination of documentation studies. Interviews and observations. The data analysis technique uses an interactive model developed by Miles & Huberman; during the data collection process, three activities are carried out: data reduction, data presentation, and verification. The implementation of the electronic identity card encountered several problems related to service to the community. These problems can be seen in the mechanism for issuing electronic identity cards that do not run optimally as expected by the community. Communication and socialization that has not been appropriately implemented. The ability of employee resources in handling electronic identity cards is not optimal.